2018
DOI: 10.1016/j.jbiosc.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation to overexpress rpaA altered photosynthetic electron transport in Synechocystis sp. PCC 6803

Abstract: Cyanobacteria are a group of prokaryotic organisms that perform oxygenic photosynthesis using a similar photosynthetic apparatus as is used in higher plants and eukaryotic algae. Cyanobacteria are also known to have a circadian rhythm. Here, we evaluated the effects on photosynthesis caused by the genetic manipulation of RpaA, which is a response regulator of a two-component regulatory system responsible for the signal output from circadian clocks. Using the unicellular cyanobacterium Synechocystis sp. PCC 680… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Specifically, RpaA is a circadian rhythm‐related transcription factor that affects gene expression patterns in a genome‐wide manner. However, previous studies demonstrated that genes encoding the components of two photosystems are basically not under the control of RpaA [37], which was consistent with the protein levels of D1 and CP1 in this study (Fig. 3C).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, RpaA is a circadian rhythm‐related transcription factor that affects gene expression patterns in a genome‐wide manner. However, previous studies demonstrated that genes encoding the components of two photosystems are basically not under the control of RpaA [37], which was consistent with the protein levels of D1 and CP1 in this study (Fig. 3C).…”
Section: Discussionsupporting
confidence: 92%
“…The results of earlier studies suggested that RpaA negatively affects PET in Synechocystis [37,38]. In the current study, RpaA decreased the electron transport from PSI to NADPH irrespective of the examined temperatures (Figs 2, 3A,B, 4, and 6A, Table 2).…”
Section: Discussionsupporting
confidence: 70%
“…One reason for this belief was the idea that organisms duplicating more than once a day do not need a rhythm longer than their life cycle ( 36 ). In the 1980's, circadian rhythm was found present in cyanobacteria ( 37 39 ), photoautotrophic organisms that produce oxygen by photosynthesis as plants and eukaryotic algae ( 40 , 41 ). In cyanobacteria, photosynthesis occurs in daylight, whereas nitrogen production peaks during the night ( 42 ).…”
Section: Circadian Rhythms Of Immune Effectors Pathogens and Vectorsmentioning
confidence: 99%
“…Regarding cyanobacteria, the central biochemical oscillator of their circadian rhythm is represented by three proteins encoded by the KaiABC cluster ( 10 , 46 , 47 ), SasA, CikA, and RepA, which control the timing training, and output of the cyanobacterial cell signaling process ( 48 ). Several studies have examined how functions the circadian loop of cyanobacteria ( 40 , 42 , 49 51 ). A theoretical model of the KaiABC oscillator suggests that ATP hydrolysis is a driving mechanism of phosphorylation oscillations and that the frequency of ATP hydrolysis in individual KaiC molecules is correlated with the circadian rhythm frequency ( 50 ) ( Figure 2 ).…”
Section: Circadian Rhythms Of Immune Effectors Pathogens and Vectorsmentioning
confidence: 99%